Intervention effects on dietary intake among children by maternal education level: results of the Copenhagen School Child Intervention Study (CoSCIS). Issue 6 (6th March 2015) - Jensen, Britt W.; von Kappelgaard, Lene M.; Nielsen, Birgit M.; Husby, Ida; Bugge, Anna; El-Naaman, Bianca; Andersen, Lars B.; Trolle, Ellen; Heitmann, Berit L.
Abstract : Dietary intake among Danish children, in general, does not comply with the official recommendations. The objectives of the present study were to evaluate the 3-year effect of a multi-component school-based intervention on nutrient intake in children, and to examine whether an intervention effect depended on maternal education level. A total of 307 children (intervention group: n 184; comparison group: n 123) were included in the present study. All had information on dietary intake pre- and post-intervention (mean age 6·8 and 9·5 years for intervention and comparison groups, respectively) assessed by a 7-d food record. Analyses were conducted based on the daily intake of macronutrients (energy percentage (E%)), fatty acids (E%), added sugar (E%) and dietary fibre (g/d and g/MJ). Analyses were stratified by maternal education level into three categories. Changes in nutrient intake were observed in the intervention group, mainly among children of mothers with a short education ( < 10 years). Here, intake of dietary fibre increased (β = 2·1 g/d, 95 % CI 0·5, 3·6, P = 0·01). Intake of protein tended to increase (β = 0·6 E%, 95 % CI − 0·01, 1·2, P = 0·05), while intake of fat (β = − 1·7 E%, 95 % CI − 3·8, 0·3, P = 0·09) and SFA (β = − 0·9, 95 % CI − 2·0, 0·2, P = 0·10) tended to decrease. Also, a significant intervention effect was observed on the intake of SFA among children of mothers with a long education (β = − 0·8, 95 % CI − 1·5, − 0·03, P = 0·04). This multi-component school-based intervention resulted in changes in the dietary intake, particularly among children of mothers with a short education. As the dietary intake of this subgroup generally differs most from the recommendations, the results of the present study are particularly encouraging.